Quebec Decision Rule in Determining the Need for Radiography in Reduction of Shoulder Dislocation; a Diagnostic Accuracy Study - Bolvardi, Ehsan; Alizadeh, Behnaz; Foroughian, Mahdi; Abbasi, Bita; Habibzadeh, Seyed Reza; Akhavan, Reza (Archives of Academic Emergency Medicine, 2019)
Introduction: The Quebec Decision Rule (QDR) has been developed for deciding on the necessity of radiography for patients with shoulder dislocation. This study aimed to investigate the diagnostic value of QDR in this regard. Method: This diagnostic accuracy study was conducted on patients with shoulder dislocation visiting the emergency department. After filling out the QDR-based checklist for all patients, they underwent radiography and the obtained radiography results were compared to QDR-based clinical diagnostic findings. Results: ‌ 143 patients with the mean age of 32.1±12 years were evaluated (88.8% males). Sensitivity, specificity, and positive and negative predictive values of QDR were 50%, 58.2%, 3.3%, and 97.6%, respectively. The sensitivity and specificity were 100% and 50% in patients >40 years old, and 33.3% and 59.8% in those <40 years old. These indices were 33.3% and 60.4%, respectively, in the male sex and 100% and 40% in the female sex. Conclusion: ‌ Quebec decision rule holds promise to diagnose concomitant fractures in patients over the age of 40 with 100% sensitivity, thereby reducing the number of radiographies by 50% without causing diagnostic errors. In contrast, this criterion proved inefficient in patients younger than 40. ‌